Exploring Push-Pull Factors Affecting Iranian Jews’ Emigration to Palestine, 1925-1954: A Social History Approach - Mousavi Dalini, Javad; Yousefi, Arash (Al-Jami'ah Research Centre, 2023)
One of the controversial issues in the twentieth century was the mass immigration of Jews around the world to Palestine/Israel. For the majority of Jews who immigrated from Europe to Palestine/Israel, immigration represented an ideological paradigm constituted by two significant factors, namely race/religion and land. However, for the large proportion of Jews coming from eastern territories, such as Iranian Jews, immigration was mainly a phenomenon affected by conflicts between socio-economic conditions in their countries of origin and those in the destination. The purpose of this study is to investigate the emigration of Iranian Jews to Palestine by relying on a pull-push framework. The study argues that socio-economic turmoil in Iran and the unfavourable economic conditions affecting Jews, along with discrimination against them, were the push factors in their country of origin. Meanwhile, the pull factors in the destination were Palestine’s economic attractiveness, Jews’ need for an increasing Jewish population in Palestine to deal with Arab nations’ sanctions, and the importance of employing an incoming workforce to handle the country’s domestic problems in terms of economy, agriculture, and materials management in the first six years after the establishment of the Israel state.[Salah satu isu kontroversial di abad kedua puluh adalah imigrasi massal orang-orang Yahudi di seluruh dunia ke Palestina/Israel. Bagi mayoritas orang Yahudi yang berimigrasi dari Eropa ke Palestina/Israel, imigrasi mewakili paradigma ideologis yang dibentuk oleh dua faktor penting, yaitu ras/agama dan tanah. Namun, bagi sebagian besar orang Yahudi yang datang dari wilayah timur, seperti orang Yahudi Iran, imigrasi terutama merupakan fenomena yang dipengaruhi oleh kesenjangan antara kondisi sosial ekonomi di negara asal dan negara tujuan. Penelitian ini bertujuan untuk mengetahui emigrasi Yahudi Iran ke Palestina berdasarkan faktor-faktor pendorong-penariknya. Penulis berpendapat bahwa gejolak sosial-ekonomi di Iran dan kondisi ekonomi yang tidak menguntungkan orang-orang Yahudi, serta diskriminasi terhadap mereka, merupakan faktor pendorong di negara asal mereka. Sementara itu, faktor penarik dari destinasinya adalah daya tarik ekonomi Israel, kebutuhan masyarakat Yahudi akan peningkatan populasi Yahudi di Israel untuk menghadapi sanksi negara-negara Arab, dan pentingnya menambah tenaga kerja baru untuk menangani permasalahan domestik negara tersebut dari segi perekonomian. pertanian, dan pengelolaan material dalam enam tahun pertama setelah berdirinya negara Israel.]